The impact of side and top arm techniques during the backstroke breakout phase on 15-meter swimming performance - Zhenyu Jin; Yuhang Zhou; Dapeng Wang; Yuhong Wen (PeerJ)
Background Research on the swimming starts and turns in professional swimming has become increasingly refined. The breakout phase is a crucial transition from point between underwater and above-water movements. The side arm technique is commonly used during the backstroke breakout phase. However, some swimmers have also achieved good performance using the top arm technique. The impact of the two techniques during the backstroke breakout phase is yet to be explored. Purpose To compare the velocity and key angles differences between the side arm and top arm techniques and analyze their effect on the first 15-m performance after push-off. Methods The subjects were 16 high-level swimmers: eight males (20.4 ± 1.6 yr) and eight females (20.9 ± 1.7 yr). Of these, 14 were backstrokers or had individual medley as their primary event. The best performances in the history of the sport’s level World Aquatics Points are 682.1 ± 59.0 and 729.3 ± 41.5 for males and females, respectively. A within-subject design was used to test both the side arm and top arm techniques. Four underwater cameras were used to capture two-dimensional data from two perspectives, focusing on the breakout phase. A two-way ANOVA used to compare segment velocity, angles, and 15-m performance between the two genders and breakout techniques. Pearson’s correlation analysis was used to explore the relationship between segment velocity and 15-m performance, and hierarchical regression was employed to investigate the impact of breakout velocity on the 15-m performance. Results Both male and female swimmers exhibited a significantly faster top arm velocities of (1.72 ± 0.20 and 1.47 ± 0.16 m/s, respectively) compared to the side arm velocities (1.51 ± 0.23 and 1.29 ± 0.19 m/s, respectively) during the breakout phase. Additionally, significant differences were found between the two genders (F = 11.189, p = 0.002, η2 = 0.286) and breakout techniques (F = 8.014, p = 0.008, η2 = 0.223), with no interaction effect (F = 0.037, p = 0.849, η2 = 0.001). Furthermore, both male (R = −0.447, p = 0.109) and female (R = −0.555, p = 0.017) swimmers showed a moderate positive correlation between breakout velocity and 15-m performance, and the regression model indicated a significant impact on the 15-m performance. Conclusion The top arm technique during backstroke may offer a velocity advantage over the traditional side arm technique during the breakout phase, influencing 15-m performance. However, considering the short duration of the breakout phase, this advantage and its impact may need to be considered in conjunction with the smoothness of the transition to the subsequent phases.